Evaluation on seed quality of three soybean varieties at different maturity stages - Ali, Imad M.; Nulit, R.; Ibrahim, Mohd Hafiz; Uddin, Md. Kamal (2019)
Maturity stage is one of the most essential factors that affect the quality of seeds. Thus, the objective of this study is to evaluate the different maturity stage (R6, R7 and R8) on the seed quality in three varieties of soybeans which are AGS190, Cikurai and Willis. By understanding the appropriate stage of maturity. This study was conducted at Faculty of Agriculture, University Putra Malaysia with the combination of two factors (2 - factorial experiment), which are varieties (AGS190, Cikurai and Willis) in three maturity stages such as R6 (Full seed stage), R7 (physiological maturity period) and R8 (Fully maturity stage) and arranged in a complete randomized design (CRD) with three replicates. The result of this study showed moisture content and EC is highest in R6 followed by R7 and R8. Consequently, germination performance and early seedling growth found lower in R6 stage. R7 is the ideal harvesting stages for all three varieties of soybean. Cikurai gives the highest germination percentage at both R7 and R8, while Wills gives the maximum germination rate index and seedling vigor index.